Reduksi Perilaku Bolos Sekolah (Studi Tentang Kerja Sama Guru PAI dan IPS di MTs PAI Medan) - Rahmat Rifai Lubis; Rasyid Anwar Dalimunthe; Ruslan Efendi (Intiqad: Jurnal Agama dan Pendidikan Islam, 2020)
This study aims to analyze (1) the background of the emergence of school skipping behavior, (2) the collaboration pattern of social studies teachers and PAI in overcoming school skipping behavior, (3) the obstacles faced in overcoming these behaviors. The research method used is qualitative with a case study approach. Data collection through observation, interviews, and documentation. The results showed that there are two underlying factors, namely internal factors, such as laziness in learning, dislike learning, feeling unimportant with learning, inability to participate in learning, mistakes in learning orientation. While external factors include the influence of friends, internet addiction, discomfort with teachers, loss of family control, neighborhood. The pattern of cooperation is to provide guidance, make a program of activities ' I'm ashamed to skip school', Working together in designing learning material formulations, applying cognitive moral strategies, engineering the environment and school relationships, limiting student relationships, establishing cooperation with parents, giving punishment. The obstacles faced are the lack of parental attention, lack of household harmony, the difficulty of providing awareness to the local community